Quasi-static tests on RC building columns strengthened with CFRP - Golubka Nechevska-Cvetanovska, Artur Roshi, Julijana Bojadjieva, Jordan Bojadjiev, Zoran Trajcevski (Croatian Association of Civil Engineers, 2021)
To explore the possibilities and benefits of using CFRP (Carbon Fibre Reinforced Polymers) in strengthening RC building columns, quasi-static tests (compression and bending) were carried out at the Institute of Earthquake Engineering and Engineering Seismology - IZIIS, Skopje by variation of concrete class, reinforcement percentage and by using various strengthening technologies. Some recommendations and outcomes regarding the approach, technology and conclusions drawn from practical application of these materials, are given. Based on the analysis of values obtained from nonlinear static and nonlinear time history analyses, it can be concluded that the ductility capacity for displacement of model strengthened with CFRP is greater by 60 %, while its strength capacity is greater by 7.7 % when compared to the values obtained for the model without CFRP. It can generally be concluded that CFRP systems are a very practical tool for strengthening and retrofitting concrete structures, as they can extensively improve flexural strengthening, shear strengthening, column confinement, and ductility.